Absence of Fc epsilonRI alpha chain results in upregulation of Fc gammaRIII-dependent mast cell degranulation and anaphylaxis. Evidence of competition between Fc epsilonRI and Fc gammaRIII for limiting amounts of FcR beta and gamma chains. - D Dombrowicz; V Flamand; I Miyajima; J V Ravetch; S J Galli; J P Kinet (The Journal of Clinical Investigation, 1997)
In mouse mast cells, both Fc epsilonRI and Fc gammaRIII are alpha beta gamma2 tetrameric complexes in which different alpha chains confer IgE or IgG ligand recognition while the signaling FcR beta and gamma chains are identical. We used primarily noninvasive techniques (changes in body temperature, dye extravasation) to assess systemic anaphylactic responses in nonanesthetized wild-type, Fc epsilonRI alpha chain -/- and FcR gamma chain -/- mice. We confirm that systemic anaphylaxis in mice can be mediated largely through IgG1 and Fc gammaRIII and we provide direct evidence that these responses reflect activation of Fc gammaRIII rather than Fc gammaRI. Furthermore, we show that Fc gammaRIII-dependent responses are more intense in normal than in congenic mast cell-deficient KitW/KitW-v mice, indicating that Fc gammaRIII responses have mast cell-dependent and -independent components. Finally, we demonstrate that the upregulation of cell surface expression of Fc gammaRIII seen in Fc epsilonRI alpha chain -/- mice corresponds to an increased association of Fc gammaRIII alpha chains with FcR beta and gamma chains and is associated with enhanced Fc gammaRIII-dependent mast cell degranulation and systemic anaphylactic responses. Therefore, the phenotype of the Fc epsilonRI alpha chain -/- mice suggests that expression of Fc epsilonRI and Fc gammaRIII is limited by availability of the FcR beta and gamma chains and that, in normal mice, changes in the expression of one receptor (Fc epsilonRI) may influence the expression of functional responses dependent on the other (Fc gammaRIII).